A procedure g5anchor to anchor γ 5 in Feynman diagrams for the Standard Model - Long Chen (Journal of High Energy Physics)
Abstract We present a procedure g5anchor to anchor γ 5 in the definition of a Dirac trace with γ 5 in Dimensional Regularization (DR) in Feynman diagrams for the Standard Model, based on a recent revision of the works by Kreimer, Gottlieb and Donohue. For each closed fermion chain with an odd number of primitive (i.e. not-yet-clearly-defined) γ 5 in a given Feynman diagram, g5anchor returns a definite set of anchor points for γ 5, in terms of pairs of ordered fermion propagators; at each of these γ 5 anchor points a fixed expression in terms of the Levi-Civita tensor and elementary Dirac matrices will be inserted together with a sign determined by anticommutatively shifting all γ 5 from their original places (dictated by the Feynman rules) to this anchor point. The defining expressions for the cyclic γ 5-odd Dirac traces in DR associated with closed fermion chains in amplitudes, or more generally squared amplitudes, thus follow from this procedure, where the Levi-Civita tensors are not necessarily treated strictly in 4-dimensions. We propose utilizing this definition in practical perturbative calculations in the Standard Model at least to two-loop orders with the current implementation. Certain limitations and modifications of the KKS and/or the Kreimer scheme are addressed, as well as the possible caveats with g5anchor.